Magnetic local time (MLT) dependence of auroral peak emission height and morphology - N. Partamies; D. Whiter; K. Kauristie; S. Massetti (Annales Geophysicae, 2022)
We investigate the bulk behaviour of auroral structures and peak emission height as a function of magnetic local time (MLT). These data are collected from the Fennoscandian Lapland and Svalbard latitudes from seven identical auroral all-sky cameras (ASC) over about one solar cycle. The analysis focusses on green auroral emission, which is where the morphology is most clearly visible and the number of images is the highest. The typical peak emission height of the green and blue aurora varies from 110 km on the nightside to about 118 km in the morning MLT over the Lapland region. It stays systematically higher (at 118–120 km) at high latitudes (Svalbard) during the nighttime and reaches 140 km at around magnetic noon. During high solar wind speed (above 500 km s −1 ), nightside emission heights appear about 5 km lower than during slow solar wind speed (below 400 km s −1 ). The sign of the interplanetary magnetic field (IMF) has nearly no effect on the emission heights in the night sector, but the northward IMF causes lower emission heights at dawn over Lapland and during the noon hours over Svalbard. While the former is interpreted as a change in the particle population within the field-of-view (FoV), the latter is rather due to the movement of the cusp location due to the IMF orientation. The morning sector heights also show a pronounced difference when previously detected pulsating aurora (PsA) events have been excluded/included in the dataset, suggesting that this type of aurora is a dominant phenomenon in the morning and an important dissipation mechanism. An increase of complex auroral structures in the midnight hours agrees with the average substorm occurrence. This increase is amplified during stronger solar wind driving and during higher geomagnetic activity (as measured by auroral electrojet index, AL). During high solar wind speed, the high latitude auroral evolution shows particularly complex morphology, which is not limited to the nightside but rather only excludes the magnetic noon hours. An increase ...